PENGARUH RELIGIUSITAS DAN REPUTASI TERHADAP MINAT MUZAKKI DALAM MEMBAYAR ZAKAT PROFESI (Studi Kasus di Kabupaten Ponorogo) - Setiawan, Fery (Universitas muhammadiyah palembang, 2018)
This study aims to analyse the factors that influence the interest of muzakki in paying zakat profession through zakat institution. The constructs used in this study are religiosity and reputation as the variables used in measuring the interest. This research was conducted in Ponorogo district. The research method used in this research is quantitative. The researcher approaches this study with survey method, in which the scale of instrument measurement used is the Likert scale as well as using purposive technique in sampling. The data analysis technique used in this research is regression analysis and the data is processed by using SPSS for windows version 20. The results of this study indicate that the factor of religiosity and reputation have a statistically significant effect on the interest of muzakki in paying zakat profession through zakat institution in Ponorogo district.